BANK'S RESPONSIBILITY FOR THE EXECUTION OF AUCTIONS FOR UNCERTIFIED LAND - Kamaleng, Eduard; Abra, Emy Hajar; Hadiyanto, Alwan (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The auction method is typically used to bring together two parties in a legal transaction. In an auction, there are two parties involved: the party submitting the bid and the party that wins the auction. Auctions can be carried out on land that has been obtained and registered with a mortgage. In practice, there are also irregularities in the auction process, particularly in auctions conducted on land that has not been certified. This is the case, for example, in Court Decision Number 03/Pdt. Eks / 2020 / Pn.Tbk Jo. Number 29 / Pdt.G / 2015 / Pn.Tbk. This study will discuss the Implementation of Regulations regarding the execution of auctions for land collateral that has not been certified. How is the Bank's Accountability for the Execution of Auctions for Land That Has Not Been Certified? What is the Solution to the Execution of Auctions for Land That Has Not Been Certified? The research methodology employed in this study is a normative research approach. Regulations governing the Execution Auction include Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units, and Land Registration, Auction PMK, Mortgage Law, Regulation of the Minister of Agrarian Affairs Number 16 of 2021 concerning the Third Amendment to the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning Implementing Provisions of Government Regulation Number 24 of 1997 concerning Land Registration. The role of the bank in the smooth running of the transfer of rights from the bank as the applicant for the auction of land to the auction winner is part of the bank's responsibility, as referred to in the theory of strict liability, which requires the bank to be jointly responsible for it even though the bank did not make a mistake. To address the issue of auction execution on uncertified land, several legal solutions can be employed. First, the government needs to accelerate the land certification process through the Systematic Land Registration (PTSL) program. Second, there needs to be stricter regulations related to auction execution. Third, education and socialization to the community regarding land rights and applicable legal procedures are also critical. Fourth, establishing mediation or dispute resolution institutions at the local level can be an alternative solution to resolving disputes that arise from auction execution. Fifth, the government should also consider providing incentives for landowners who are willing to undergo certification.